Types of Derivational Suffixes Found in “The Girl Who Fell Beneath the Sea” Novel - Ni Ketut Yesy Alita Pradnyantari; I Gusti Bagus Wahyu Nugraha Putra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The aim of this study is to analyze the types of derivational suffixes found in the novel “The Girl Who Fell Beneath the Sea” by Axie Oh, which was selected because its rich use of descriptive language and modern narrative style. Morphology, as a branch of linguistics, focuses on the structure and formation of words. One important part of morphology is the use of derivational suffixes. This study focuses on identifying and classifying these suffixes into four types: adjectival, adverbial, nominal, and verbal. The theory used in this study is based on Plag (2002) and McCarthy (2002), which explained the classification and functions of derivational suffixes. This study uses a qualitative method with an observation technique. The data were collected by reading the first three chapters of the novel, identifying words with derivational suffixes, and grouping them using labelling and bracketing. The result showed 214 derivational suffixes, with adjectival suffixes occurring most frequently, indicating that adjectival derivation has an important role in shaping descriptive expressions in the novel.